Megan Osborne and Linda Carlson at Avenir Museum opening gala - Unidentified photographer (Colorado State University. Libraries, 2016)
Photograph of Assistant Curator and Collections Manager Megan Osborne and Curator Emeritus Linda Carlson posing at the opening gala for the new Avenir Museum of Design and Merchandising building on January 29, 2016.
Keywords: Fashion -- History; Fashion -- Exhibitions